MANAGEMENT OF SPECIAL CONSERVATION VALUES: APPROACHES AND PROCESSES IN ACCORDANCE WITH FSC CERTIFICATION REQUIREMENTS - Pavlishchuk, Oksana; Churilov, Andrii; Kravets, Pavlo (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
Approaches to the management system necessary to ensure the proper implementation of the requirements of the FSC Forest Management System Standard for Ukraine in terms of special conservation values are presented in the paper. The emphasis is on systemic, process, adaptive and risk-based approaches to management in connection with the specific requirements of the specified standard, the implementation of which they contribute to. The processes are highlighted, the formation and implementation of which is the basis for achieving goals for special conservation values. The components of interaction with stakeholders on issues related to special conservation values ​​are presented as an element of openness and transparency of the management system in accordance with FSC requirements.